Current knowledge in lentil genomics and its application for crop improvement - Kumar, Shiv; Rajendran, Karthika; Kumar, Jitendra; Hamwieh, Aladdin; Baum, Michael (Frontiers in Plant Science, 2015)
Most of the lentil growing countries face a certain set of abiotic and biotic stresses causing substantial reduction in crop growth, yield, and production. Until-to date, lentil breeders have used conventional plant breeding techniques of selection-recombination-selection cycle to develop improved cultivars. These techniques have been successful in mainstreaming some of the easy-to-manage monogenic traits. However in case of complex quantitative traits, these conventional techniques are less precise. As most of the economic traits are complex, quantitative and often influenced by environments and genotype-environment (GE) interaction, the genetic improvement of these traits becomes difficult. Genomics assisted breeding is relatively powerful and fast approach to develop high yielding varieties more suitable to adverse environmental conditions. New tools such as molecular markers and bioinformatics are expected to generate new knowledge and improve our understanding on the genetics of complex traits. In the past, the limited availability of genomic resources in lentil could not allow breeders to employ these tools in mainstream breeding program. The recent application of the Next Generation Sequencing (NGS) and Genotyping by sequencing (GBS) technologies has facilitated to speed up the lentil genome sequencing project and large discovery of genome-wide SNP markers. Recently, several linkage maps have been developed in lentil through the use of Expressed Sequenced Tag (EST)-derived Simple Sequence Repeat (SSR) and Single Nucleotide Polymorphism (SNP) markers. These maps have emerged as useful genomic resources to identify QTL imparting tolerance to biotic and abiotic stresses in lentil. In this review, the current knowledge on available genomic resources and its application in lentil breeding program are discussed.